Challenges and supporting factors in implementing the STAD strategy in English language teaching at SMP Pesantren as-Salam Pontianak - Claudia, Cindy; Citra Kusumaningsih; Irwan, Dedi (Journal of English Language Proficiency, 2025)
The purpose of this study is to find out what are the challenges felt by teachers in applying the student team achievement divisions (STAD) strategy in teaching English and the supporting factors in applying the student team achievement divisions (STAD) strategy in teaching English. This qualitative research uses descriptive-qualitative methods. This research involves one teacher and students in grade 8. Data were collected through interviews and documentation methods. The research findings revealed two challenges in implementing the student team achievement divisions (STAD) strategy in teaching English: limited access to facilities and technology at school, and time constraints. As for the supporting factors in implementing the student team achievement divisions (STAD) strategy in teaching English, the researcher's findings were teacher competence and school facilities. This research is intended to be a valuable resource for educators exploring innovative strategies for teaching English